Moon rising - Sutherland, Tui T. (Wings of fire, 2015)
Peace has come to Pyrrhia... for now.The war between the tribes is finally over, and now the dragonets of the prophecy have a plan for lasting peace: Jade Mountain Academy, a school that will gather dragonets from all the tribes and teach them to live together, perhaps even as friends.Moonwatcher isn't sure how she feels about school, however. Hidden in the rainforest for most of her life, the young NightWing has an awful secret. She can read minds, and even see the future. Living in a cave with dozens of other dragons is noisy, exhausting -- and dangerous. In just a few days, Moon finds herself overwhelmed by her secret powers and bombarded by strange thoughts, including those of a mysterious dragon who might be a terrible enemy. And when someone starts attacking dragons within the academy, Moon has a choice to make: Stay hidden and safe? Or risk everything to save her new friends?